2018
DOI: 10.1111/1748-8583.12209
|View full text |Cite
|
Sign up to set email alerts
|

Employers' organisations as social movements: Political power and identity work

Abstract: The literature on employers' and business organisations (EOs) has failed to analyse them as contentious organisations that apply identity work as a power resource to mobilise resources and members. This article is based on a qualitative case study of Islamic EOs in Turkey. Developing a social movement model of EOs, I analyse the mechanisms through which identity work with local religious collaborators facilitated collective action and political power. I find that the role of identity work was threefold: provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…EOs' main functions were once to counter trade union power and conduct collective bargaining, but the decline of these institutions raised concerns as to the continued existence of EOs. However, researchers pointed to the “strange non‐death of employer associations” (Brandl & Lehr, ) to debate the continuing relevance of EOs (Ibsen & Navrbjerg, ; Sezer, ). This article contributed to this debate by arguing that EOs adapted to changing socio‐economic contexts by evolving within and across three roles—as an IR actor, a political actor and a service provider.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EOs' main functions were once to counter trade union power and conduct collective bargaining, but the decline of these institutions raised concerns as to the continued existence of EOs. However, researchers pointed to the “strange non‐death of employer associations” (Brandl & Lehr, ) to debate the continuing relevance of EOs (Ibsen & Navrbjerg, ; Sezer, ). This article contributed to this debate by arguing that EOs adapted to changing socio‐economic contexts by evolving within and across three roles—as an IR actor, a political actor and a service provider.…”
Section: Resultsmentioning
confidence: 99%
“…Historical accounts attest to the role of EOs in breaking strikes, locking out trade unionists, and recruiting strike‐breakers often with the cooperation of state authorities (Grant & Wallace, ). Similar methods continued in countries with weakly institutionalised systems of IR, for example, in Turkey where Islamic EOs resisted trade unionism, even when such organisations possessed an Islamic character (Sezer, ).…”
Section: Eos As Industrial Relations Actormentioning
confidence: 99%
“…Unions need narratives that instill a sense of efficacy, that is, that they can be successful, despite the sometimes dire structural challenges. In a similar vein, employer organizations may use identity work as a power resource to mobilize resources and members (Sezer, 2019). Rather than static and hegemonic, ideas and identities guide agency in labor markets, as they give meaning to the strategic choices of ER-actors in seeking to regulate employment.…”
Section: De At Iona L Sc Hol a R Sh I P I N A N E M Ploy M E N T R E L At Ions Con T E Xt: M Ac Ro M E So M Ic Romentioning
confidence: 99%
“…Swank and Martin (2001) found that the centralization of national business associations, the amount of cohesion among employer groups and the level of economic cooperation across enterprises were significant determinants of total social welfare effort. These outcomes were not only the result of sanctions and interest aggregation, but also of associations’ impact on their members’ cognitive orientations and solidarity (Sezer, 2019). Martin and Swank (2012, pp.…”
Section: Firm Cooperation and Competitionmentioning
confidence: 99%